2010
DOI: 10.1021/jf100017e
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, Translocation, and Remobilization of Zinc Absorbed at Different Growth Stages by Rice Genotypes of Different Zn Densities

Abstract: Zinc (Zn) is an essential micronutrient for humans, and increasing Zn density in rice ( Oryza sativa L.) grains is important for improving human nutrition. The characteristics of Zn translocation and remobilization were investigated in high Zn density genotype IR68144, in comparison with the low Zn density genotype IR64. Stable isotope tracer (68)Zn was supplied at various growth stages, either to the roots in nutrient solution or to the flag leaves to investigate the contribution of (68)Zn absorbed at differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
2
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(124 citation statements)
references
References 32 publications
4
112
2
6
Order By: Relevance
“…Remobilization of Fe and Zn increased when these micronutrients were withheld from the hydroponic solution post-anthesis, indicating that remobilization mechanisms might be upregulated under nutrient limitation [24]. In this wheat study, flag leaf and lower leaves were the major sources of remobilized micronutrients, in contrast to results from rice, where stems accounted for the major source of Zn remobilized to grain [13]. In another rice study, the authors concluded that remobilization accounted for very little grain Zn, and that uptake after anthesis supplied the majority of Zn to grain, with most Zn passing through stems, and only a small amount passing through leaves [25].…”
Section: Remobilization or Continuous Uptake?contrasting
confidence: 47%
See 1 more Smart Citation
“…Remobilization of Fe and Zn increased when these micronutrients were withheld from the hydroponic solution post-anthesis, indicating that remobilization mechanisms might be upregulated under nutrient limitation [24]. In this wheat study, flag leaf and lower leaves were the major sources of remobilized micronutrients, in contrast to results from rice, where stems accounted for the major source of Zn remobilized to grain [13]. In another rice study, the authors concluded that remobilization accounted for very little grain Zn, and that uptake after anthesis supplied the majority of Zn to grain, with most Zn passing through stems, and only a small amount passing through leaves [25].…”
Section: Remobilization or Continuous Uptake?contrasting
confidence: 47%
“…In pea (Pisum sativum), 59 Fe applied to leaflets, stipules, and pod walls was translocated into seeds [11]. In wheat and rice, 65 Zn applied to leaf tips was translocated to grain [12,13]. Foliar Zn fertilization was highly effective at increasing Zn concentration in wheat grain, especially when applied at various times during the grain filling period [1,14].…”
Section: Which Tissues Supply Micronutrients To Seeds and At Which Dmentioning
confidence: 99%
“…For example, Wu et al (2010) studied the uptake, translocation, and remobilization of Zn absorbed at different growth stages by rice genotypes of different Zn densities using Zn 68 stable isotope tracer. They found that significant differences in Zn allocation existed between two rice genotypes.…”
Section: Iron and Zinc Uptake Accumulation And Translocation To mentioning
confidence: 99%
“…In soybean and wheat, seed/grain Mg appears to be mobilized from leaves, partially because of its high phloem mobility (Maillard et al 2015). Zinc is also essential for rice plants, and more than half of grain Zn is remobilized from that accumulated and stored in leaf, sheath, and stem before anthesis (Wu et al 2010;Yilmaz et al 2016). In this study, a considerable contribution rate of Mg and Zn nutrients of the bracts was detected, with values as high as 12.56 and 12.34%, respectively, in comparison with that of the leaf (16.58 and 9.79%), and sheath (18.27 and 26.67%).…”
Section: Remobilization Of Mineral Nutrients From Bracts To Grainmentioning
confidence: 99%